The effect of using concept maps in collecting violations and errors in the law of the basketball game (Journal of the College of Basic Education, 2022)
The researchers used the strategy of concept maps, which is one of the teaching strategies that emerged from the theory of (Ozbel), to identify the impact of the strategy on student achievement in irregularities and mistakes from the basketball law for the second stage in the College of Physical Education / Al-Mustansiriya University.The research aims to:1- The use of concept maps in teaching the vocabulary of basketball law (violations and fouls) to increase student achievement.